2021
DOI: 10.1177/09610006211036729
|View full text |Cite
|
Sign up to set email alerts
|

Information poverty predictors among Ahvazi citizens; Investigating some cases

Abstract: The present study aimed to investigate the most important information poverty predictors among Ahvazi citizens. This applied and correlational-descriptive study employed structural equation modeling to analyze the data. The information poverty scale and the standard questionnaires of social participation, social exclusion, technophobia, and economic capital were used to collect the data. On the next step, their reliability and validity were confirmed through using Cronbach’s alpha and confirmatory factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In the extant literature, many of the studies on the predictors of poverty only identify global drivers while glossing over local predictors (Dartanto & Nurkholis, 2013; Farajpahlou et al, 2021; Garza‐Rodriguez et al, 2021; Gong et al, 2022; Mdluli & Dunga, 2022; Wang & He, 2020). Therefore, these studies conclude that the predictors of poverty are geographically uniform.…”
Section: Introductionmentioning
confidence: 99%
“…In the extant literature, many of the studies on the predictors of poverty only identify global drivers while glossing over local predictors (Dartanto & Nurkholis, 2013; Farajpahlou et al, 2021; Garza‐Rodriguez et al, 2021; Gong et al, 2022; Mdluli & Dunga, 2022; Wang & He, 2020). Therefore, these studies conclude that the predictors of poverty are geographically uniform.…”
Section: Introductionmentioning
confidence: 99%
“…"Access gap" emphasizes people's differences in the accessibility of the Internet infrastructure from the technical level, whereas "use gap" refers to people's differences in technical skills when obtaining and using information from the application viewpoint [3,4]. Under the in uence of the directional decomposition of "information poverty," some scholars have deconstructed information poverty into multiple dimensions and they believe that it can be comprehensively measured from the information reception, information utilization, and information skill perspectives [5,6]. Studies on factors in uencing the depression of multidimensional information poverty of the elderly people have reported that individual characteristics, such as age and physical tness, and family endowments, such as economic status and population, are also important players in the information behavior of the elderly people [7][8][9].…”
Section: Introductionmentioning
confidence: 99%